COMMUNICATIVE TASKS FOR A MONOLOGUE FORM OF COMMUNICATION DEVELOPMENT IN FOREIGN LANGUAGE LESSONS FOR STUDENTS AT THE SENIOR STAGE OF SECONDARY SCHOOL - Ravshanbekova Munisa Khamidjanovna; Golovchun Aleftina Anatolyevna (Modern Scientific Technology, 2025)
Developing monologue speech in foreign language learning is crucial for students to achieve communicative competence. This article explores the effectiveness of communicative tasks aimed at enhancing monologue communication skills among senior secondary school students. A quantitative approach was employed, using questionnaires to collect data on students’ perceptions, fluency, coherence, and confidence levels before and after task implementation. The results indicate that communicative tasks positively impact students’ ability to deliver structured monologues, with improvements in speech organization and self-assurance. The study highlights the need for well-designed speaking tasks tailored to learners’ proficiency levels to maximize their language potential.